The effect of red and far-red light on the germination of seeds of four species of Philippine plants - Venturina, Josefina Y Dela Fuente, 1934-
Certain conditions of moisture, temperature, oxygen, and in some cases, light must be made available before seeds can germinate. In seeds that require light, it has been shown that red light stimulates and far-red light inhibits germination. This study investigated the effects of red and far-red light on the germination of seeds of four species of Philippine plants growing in the U.P. (Q.C.) Campus. Results obtained from this study showed that the seeds of Tridax procumbens are light-sensitive, i.e., promoted by red and inhibited by far-red light, while those of Chloris barbata (Kurus-Kurusan) and Impatiens balsamina (Kalamantigue) are not. The seeds of Zinnia elegans germinate equally well in the light and in the dark.